2011
DOI: 10.1016/j.avb.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the sexual fantasies of sex offenders and their correlates

Abstract: Sexual fantasy is proposed to be an important factor in sexual offending. However, the existing research on this topic suggests that its role is multifaceted and interrelated with various other important factors associated with the sex offender. Thus, in this paper, we begin by examining some of the conceptual and definitional issues regarding the term ‗deviant sexual fantasy'. We then discuss the literature relating to sexual fantasies and some of its chief correlates, including: (1) sexual arousal, (2) affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 93 publications
1
51
0
2
Order By: Relevance
“…For example, Flak, Beech, and Fisher (2007) suggest that fantasies are important in the development of deviant preferences and interests and enhanced arousal. Some studies have suggested that community men and women who perpetrate sexual aggression often experience a higher frequency of deviant sexual thoughts than non-aggressors (e.g., Bartels & Gannon, 2011;Hunter, Lexier, Goodwin, Browne, & Dennis, 1993;Tardif, Auclair, Jacob, & Carpentier, 2005;Williams, Cooper, Howell, Yuille, & Paulhus, 2009). However, the lack of an operational definition of "deviant fantasy" makes it difficult to assess such fantasies with a valid measure.…”
mentioning
confidence: 99%
“…For example, Flak, Beech, and Fisher (2007) suggest that fantasies are important in the development of deviant preferences and interests and enhanced arousal. Some studies have suggested that community men and women who perpetrate sexual aggression often experience a higher frequency of deviant sexual thoughts than non-aggressors (e.g., Bartels & Gannon, 2011;Hunter, Lexier, Goodwin, Browne, & Dennis, 1993;Tardif, Auclair, Jacob, & Carpentier, 2005;Williams, Cooper, Howell, Yuille, & Paulhus, 2009). However, the lack of an operational definition of "deviant fantasy" makes it difficult to assess such fantasies with a valid measure.…”
mentioning
confidence: 99%
“…For example, a number of studies have demonstrated a relationship between deviant sexual fantasies and negative emotional/affective states (Looman, 1995;McKibben, Proulx, & Lusignan, 1994;Proulx, McKibben, & Lusignan, 1996), personality traits (Curnoe & Langevin, 2002;Williams, Cooper, Howell, Yuille, & Paulhus, 2009), behavior (MacCulloch et al 1983Woodworth, Freimuth, Hutton, Carpenter, Agar, & Logan, 2013) and cognition Zurbriggen & Yost, 2004). Thus, rather than being restricted to sexual arousal, this research suggests that deviant sexual fantasy is a much more multifaceted phenomenon (Bartels & Gannon, 2011).…”
Section: Recent Developmentsmentioning
confidence: 84%
“…As such, deviant fantasies are generally included within theories of sexual offending (e.g., Marshall & Barbaree, 1990;, relapse prevention models (Pithers, Kashima, Cummings, & Beal, 1988), and treatment programs (Stinson & Becker, 2012). However, deviant sexual fantasy is a multifaceted phenomenon that interrelates with a number of other factors such as affect, personality, and behaviour (Bartels & Gannon, 2011). Thus, deviant fantasies have been proposed (and found) to serve other functions for sex offenders.…”
Section: Introductionmentioning
confidence: 99%
“…La fantasía sexual es una cognición o conducta encubierta que implica imágenes y/o narrativas verbales excitadoras o estimulantes (Bartels y Gannon, 2011). Las fantasías sexuales pueden formar parte de una historia elaborada o representar actividades sexuales, cuerpos desnudos o áreas erógenas; pueden involucrar situaciones irreales, situaciones deseadas o construirse a partir de recuerdos e involucrar memorias episódicas.…”
Section: Introductionunclassified